Distribution of m-xylene to subcutaneous adipose tissue in short-term experimental human exposure. - Engström, Jörgen; Riihimäki, Vesa (Scandinavian Journal of Work, Environment & Health, 1979)
When volunteers were exposed in three different patterns of exposure to approximately 3.7–8.2 mumol/l (90–200 ppm, constant or time-weighted average concentration) of m-xylene for five consecutive days plus one day after the weekend, approximately 3.7–8.0% of the total body uptake was estimated to be distributed to the adipose tissue on the basis of m-xylene determinations made from subcutaneous fat. Distribution seemed to be affected by the exposure pattern; a proportionately greater distribution to subcutaneous fat occurred when the volunteers performed physical exercise part of the time, particularly when the peak xylene concentrations in the air coincided with the exercise. The median elimination half-time of m-xylene from subcutaneous fat was 58 h (range 25–128 h). A positive correlation was found between the individual elimination half-times of m-xylene in subcutaneous fat and the relative fat mass of the individuals in two exposure groups, but not in one.
Keywords: adipose tissue; distribution; experimental exposure; human exposure; m-xylene; short-term experimental human exposure; short-term exposure; subcutaneous adipose tissue